Development of Image Reconstruction Algorithm in Realtime for Compton Camera Systems - Bui, Ngoc Ha; Tran, Thuy Duong; Nguyen, Duc Kien (JST: Engineering And Technology For Sustainable Development, 2021)
Compton Camera is a imaging technique that uses the principle of Compton scattering interaction to reproduce the distribution image of the radiation source. Compton Camera is a 3-D imaging technique, which has a high sensitivity, wide viewing angle and a range of shooting energy that is much higher than the transmissive imaging technique. In addition, the Compton Camera imaging technique does not use a mechanical collimation system, so it is compact in size, suitable for mobile applications, security control, radiation source detection and medical applications. In this paper, the authors built an image reconstruction algorithm for Compton Camera imaging equipment using data from Monte Carlo simulation. The image quality and the parameters of the algorithm will be evaluated in detail to determine the practical applicability.